Pengaruh Motivasi, Kompetensi Dan Budaya Kerja Terhadap Kinerja Guru Madrasah Ibtidaiyah Dengan Kepemimpinan Sebagai Variabel Moderating - Fahmi Zakariya Al Anshori; Dikdik Harjadi; Dede Djuniardi (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Research objectives: 1)to determine the effect of work motivation on the performance. 2) to determine the effect of competence on the. 3) to determine the effect of work culture on the performance. 4) to find out whether leadership can moderate the relationship between work motivation and the performance. 5) to find out whether leadership can moderate the relationship between competence and the performance . 6) to find out whether leadership can moderate the relationship between work culture and the performance. The study population was all private madrasa teachers in Ciawigebang District, Kuningan Regency, totaling 127 Madrasa teachers. The sampling technique uses a saturated sample. The data analysis method uses SEM analysis with the SmartPLS analysis tool. The results of the study: 1) work motivation has a significant positive effect on teacher performance. 2) competence has a significant positive effect on teacher performance. 3) work culture has a positive and significant on teacher performance. 4) leadership cannot moderate the influence of work motivation on teacher performance. 5) leadership cannot moderate the influence of competence on teacher performance. 6) leadership is unable to moderate the influence of work culture on teacher performance.